Transforming Learning Through The Integration Of Islamic Values In The Era Of Merdeka Belajar - Nurjanah, Amaliya; Pahrudin, Agus; Rahmi, Sri (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2025)
This study aims to examine the transformation of the essence, principles, and objectives of education in the era of Freedom to Learn by integrating Islamic values and Islamic educational management. The concept of freedom to learn in Indonesia is known as merdeka belajar. This study was motivated by a paradigm shift in Indonesia's national education policy that emphasizes autonomy, contextual learning, and character development. Through a qualitative literature analysis approach, this study investigates the relevance and application of fundamental Islamic educational values such as adab (ethics), ikhlas (sincerity), and amanah (trustworthiness) in supporting the merdeka belajar philosophy. The results of the study indicate that these values are highly aligned with policy objectives and contribute to the formation of a more holistic and meaningful educational environment. Furthermore, the integration of Islamic educational management practices supports the development of spirituality, competencies, and independent thinking among students. This study contributes to the discourse on Islamic educational reform by providing a conceptual framework that can guide educators and policymakers in designing learning systems rooted in spirituality and responsive to context in the modern educational landscape.